Question Number 215454 by cherokeesay last updated on 07/Jan/25
Answered by mr W last updated on 07/Jan/25
Commented by mr W last updated on 15/Jan/25
$${EB}=\mathrm{2}{a} \\ $$$${EA}=\mathrm{2}{b} \\ $$$${CB}=\sqrt{\mathrm{3}}{a} \\ $$$${DA}=\sqrt{\mathrm{3}}{b} \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}×\left(\mathrm{2}{b}−{a}\right)\sqrt{\mathrm{3}}{a}=\mathrm{2}×\mathrm{8} \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}×\left(\mathrm{2}{a}−{b}\right)\sqrt{\mathrm{3}}{b}=\mathrm{2}×\mathrm{15} \\ $$$$\frac{\left(\mathrm{2}{a}−{b}\right){b}}{\left(\mathrm{2}{b}−{a}\right){a}}=\frac{\mathrm{15}}{\mathrm{8}} \\ $$$$\mathrm{15}{a}^{\mathrm{2}} −\mathrm{14}{ab}−\mathrm{8}{b}^{\mathrm{2}} =\mathrm{0} \\ $$$$\left(\mathrm{3}{a}−\mathrm{4}{b}\right)\left(\mathrm{5}{a}+\mathrm{2}{b}\right)=\mathrm{0} \\ $$$$\Rightarrow\frac{{a}}{{b}}=\frac{\mathrm{4}}{\mathrm{3}} \\ $$$$\frac{\mathrm{1}}{\mathrm{2}}×\left(\mathrm{2}×\frac{\mathrm{4}{b}}{\mathrm{3}}−{b}\right)\sqrt{\mathrm{3}}{b}=\mathrm{2}×\mathrm{15} \\ $$$$\sqrt{\mathrm{3}}{b}^{\mathrm{2}} =\mathrm{36} \\ $$$$\Rightarrow{b}=\frac{\mathrm{6}}{\:\sqrt{\sqrt{\mathrm{3}}}}\:\Rightarrow{a}=\frac{\mathrm{8}}{\:\sqrt{\sqrt{\mathrm{3}}}} \\ $$$$\Delta{ABE}=\frac{\mathrm{2}{a}×\mathrm{2}{b}\:\mathrm{sin}\:\mathrm{60}°}{\mathrm{2}}=\sqrt{\mathrm{3}}{ab}=\mathrm{48} \\ $$$$?=\mathrm{48}−\mathrm{8}−\mathrm{15}=\mathrm{25}\:\checkmark \\ $$
Commented by mr W last updated on 07/Jan/25
Commented by cherokeesay last updated on 07/Jan/25
$${so}\:{nice}\:! \\ $$$${thank}\:{you}\:{so}\:{much}\:{master}\:! \\ $$